Accessibility and Barriers to Uptake of Ophthalmic Services among Rural Communities in the Upper Denkyira West District, Ghana - Yaa Koomson Nana; Adaboh Hayford; Kyei Nkansah Ernest; Kumi Amponsah Joseph; Larbi Daniel; Odoi Odotei Samuel (Journal of Ophthalmic Science, 2019)
Vision impairment and blindness remain a challenge in developing countries, especially in rural communities. Notwithstanding, VISION 2020 global initiative seeks to eliminate avoidable blindness by 2020. This community-based cross-sectional study aimed at determining the accessibility of ophthalmic services and barriers to its utilization in rural communities in the Upper Denkyira West District, Ghana. One-hundred and seventy participants from 5 randomly chosen rural communities in the district were included. Participants were interviewed using a structured questionnaire. Socio-demographic information, information regarding accessibility, utilization, and barriers to eye care services were obtained. Descriptive statistics were carried out using SPSS version 23. The Chi-squared test was employed to determine associations. P-values less than 0.05 at a confidence interval of 95% were considered significant. Only 21.8% of participants had had eye examination within the past 3 years, with over half of the examinations undertaken at screening grounds and health centres. Significant associations were found between ophthalmic services utilization and increasing age (p = 0.004), female gender (p = 0.027) and those who had a past history of eye problem(s) (p = 0.0010. The study found gross inadequate utilization of ophthalmic services mainly due to unavailable ophthalmic services in the rural district. Public health education and eye care interventions should prioritize and target rural populations. Key Messages This study found gross inadequate utilization of ophthalmic services mainly due to unavailable ophthalmic services in the rural district. Rural dwellers were thus compelled to resort to harmful eye care practices. Public health education and eye care interventions should prioritize and target rural populations
Keywords: rural